(untitled) (Minerva, 2019)
In this paper the authoress deals with the film “The eternity and a Day”, linking it with modern Greek Lyrics, especially with the character of Dionysios Solomos, cornerstone of National Greek Poetry. His presence in the film is used as a symbol of Greek values which, in times of crisis (either individual –illness– or collective –war, immigration–) turn themselves into universal referents such as freedom and human dignity.